Analisis faktor yang mempengaruhi pendapatan tenaga kerja wanita keluarga pra sejahtera penerima PKH di Kota Jambi (Studi Kasus: Kecamatan Alam Barajo) - Tri Egi Sundari; Junaidi Junaidi; Adi Bhakti (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
The purpose of this study to determine and analyze the socioeconomic characteristics of female workers in pre-prosperous families who received PKH and To find out and analyze the effect of age, education, work experience and working hours of respondents on the income of women workers in pre-prosperous families who are PKH recipients in Alam Barajo District, Jambi City. The data used are primary data and secondary data. The method of analysis used in this research is the method of analysis used in this research is descriptive analysis method using a quantitative approach, and using multiple linear regression formulations. Based on the results of the study, it shows that the variables of working hours, age, and work experience have a significant effect on the income of women workers in pre-prosperous families who are PKH recipients. Meanwhile, the level of education has an insignificant effect on the income of women workers in poor families who are PKH recipients in Jambi City.